Preparing All Educators to Serve Students with Extensive Support Needs: An Interdisciplinary Approach. Issue 1 (3rd April 2022) - Robertson, Phyllis; McCaleb, Karen N.; McFarland, Laura A.
ABSTRACT: Despite evidence that inclusion is a research-based practice for students with extensive support needs (ESN), such students are often denied access to meaningful instruction in general education. This article describes an interdisciplinary program that prepares educators to serve all students, including those with low-incidence disabilities, in inclusive environments. Results of the needs assessment that informed program development are shared along with a description of the program model and its implementation. The goal is to ensure that candidates are equipped to not only comply with legal mandates but also meet the social justice intent of Individuals with Disabilities Education Act.